Interactions between individual plant species and soil nutrient status in Shortgrass Steppe - Burke, Ingrid C., author; Vinton, Mary Ann, author; Ecological Society of America, publisher (Colorado State University. Libraries, 1995)
The effect of plant community structure on nutrient cycling is fundamental to our understanding of ecosystem function. We examined the importance of plant species and plant cover (i.e., plant covered microsites vs. bare soil) on nutrient cycling in shortgrass steppe of northeastern Colorado. We tested the effects of both plant species and cover on soils in an area of undisturbed shortgrass steppe and an area that had undergone nitrogen and water additions from 1971 to 1974, resulting in significant shifts in plant species composition. Soils under plants had consistently higher C and N mineralization rates and, in some cases, higher total and microbial C and N levels than soils without plant cover. Four native grasses, one sedge, and one shrub differed from one another in the quantity and quality of above- and belowground biomass but differences among the six species in soil nutrient cycling under their canopies were slight. However, soils under bunchgrasses tended to have higher C mineralization and microbial biomass C than soil under the rhizomatous grass, Agropyron smithii. Also, the one introduced annual in the study, Kochia scoparia, had soils with less plant-induced heterogeneity and higher rates of C and N mineralization as well as higher levels of microbial biomass C than soils associated with the other species. This species was abundant only on plots that had received water and nitrogen for a 4-yr period that ended 20 year ago, where it has persisted in the absence of resource additions for 20 yr, suggesting a positive feedback between plant persistence and soil nutrient status. Plant cover patterns had larger effects on ecosystem scale estimates of soil properties than the attributes of a particular plant species. This result may be due to the semiarid nature of this grassland in which plant cover is discontinuous and decomposition and nutrient availability are primarily limited by water, not by plant species-mediated characteristics such as litter quality. That local plant-induced patterns in soil properties significantly affected ecosystem scale estimates of these properties indicates that consideration of structural attributes, particularly plant cover patterns, is critical to estimates of ecosystem function in shortgrass steppe.
Keywords: plant-soil feedback; nutrient cycling; nitrogen; island of fertility; functional groups; disturbance; carbon; shortgrass steppe; soil heterogeneity